(untitled) - Heertje, Arnold (London, 1977)
Contents: Introduction; The Classical economists; Marx; The beginnings of production theory; Schumpeter; Microeconomic production theory
Keywords: Technological innovations,Economic development,Đổi mới công nghệ,Phát triển kinh tế